Regioselective C–H chalcogenylation and halogenation of arenes and alkenes under metal-free conditions. Issue 14 (21st March 2023) - Li, Bin; Hu, Mingli; Ge, Jun; Xu, Wei; Wu, Jinghan; Tong, Yao; Zhao, Zhengyi; Liu, Xiuxiu; He, Ling
Abstract : The reactions of direct Csp 2 –H chalcogenylation and halogenation of N -arylpyrrolidone under the action of PIFA without a directing group and under metal-free conditions were reported in this paper. Abstract : The reactions of direct Csp 2 –H chalcogenylation and halogenation of N -arylpyrrolidone under the action of PIFA without a directing group and under metal-free conditions were reported in this paper. Diphenyl selenide/sulfur and selenium phenyl halides were used as reaction reagents to obtain chalcogenylated and halogenated N -arylpyrrolidone products, respectively. The mechanistic studies indicated that a radical pathway was likely involved in these reactions. Preliminary antitumor tests showed that these compounds have moderate to potent activities against human acute leukemia cells K562 in vitro, which may be used as lead compounds for subsequent research.